Allogenous Bone Grafting Technique for Staged Revision Anterior Cruciate Ligament Surgery - Søren Vindfeld MD; Line Lindanger MD, PhD; Eivind Inderhaug MD, MPH, PhD (SAGE Publishing, 2023)
Background: Tunnel widening, slightly malplaced former tunnels or bone loss due to hardware removal might prevent a 1-stage anterior cruciate ligament (ACL) revision procedure due to tunnel convergence or challenging graft fixation. A range of graft sources and bone grafting techniques are described-all with their strengths and limitations. Common autograft techniques come with substantial donor site morbidity that might hinder postoperative rehabilitation. Indications: Graft tunnel issues might prompt the need for structural grafts and a 2-stage ACL revision approach. The use of the current dowel allograft technique gives a flexible approach where 1 or several cylindrical grafts can be placed in prepared sockets for reliable bony ingrowth. Technique Description: Using femoral head allografts and cannulated coring reamers, multiple bone dowels (up to 6) can give a flexible and adaptable bone grafting situation. The intra-articular tunnels are dilated, and dowels are produced to allow a press-fit fixation that facilitates good bone healing. Removal of sclerotic bone and microfracture is key to allow optimal bone-to-bone healing. Use of cannulas inserted through the arthroscopic portals and tamps plug advancement will give a reliable graft deployment without dowel breakage. Results: The current authors have used this uniform technique for 119 patients since 2014. All cases displayed good bony healing at 5 months after surgery on computed tomography and radiographs, and 115 out of 119 went on to have a stage 2 revision ACL surgery at 6 months spacing from the bone grafting. The most common reason for not going through the second-stage revision was improvement of symptoms due to graft removal and bone grafting during the first surgery. Discussion/Conclusion: The current allograft dowel bone grafting allows for a flexible bone grafting in cases where a 1-step ACL revision procedure is not feasible. Reliable bony ingrowth is seen in the current cohort allowing the final step of ACL revision at 6 months spacing from bone grafting. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.